HUBUNGAN JENIS PERSALINAN DAN STATUS ANEMIA IBU BERSALIN DENGAN KEJADIAN ASFIKSIA NEONATORUM - Hidayati, Nurma; Susanti, Tri (Jurnal Kesehatan, 2023)
Based on WHO data in 2003, infant mortality occurred at the age of the neonate due to asphyxia ortrauma by 28%. The purpose of this study was to determine the relationship between the type of deliveryand anemia status of pregnant women with the incidence of neonatal asphyxia at Abdoel MoloekHospital. This study used analytic methods with a cross-sectional study design. The population in thisstudy were all mothers giving birth, namely 1363, using stratified random sampling with a sample of309 consisting of 96 asphyxia cases and 213 cases without asphyxia. This study uses secondary datawith a checklist tool. The formula used is univariate or frequency distribution and bivariate with the chisquare formula. The results showed that 181 (58.58%) mothers gave birth to asphyxia babies and 195(63.11%) mothers had anemia. Based on the chi-square analysis, there is a relationship between thetype of delivery and the incidence of asphyxia with a p-value (0.017) < α (0.05) and there is arelationship between the anemia status of the mother and the incidence of asphyxia with a p-value(0.007) < α (0, 05). The conclusion from the research results of mothers who gave birth to asphyxiababies were the majority of assisted births and mothers who experienced anemia. So it is hoped that thehospital can improve better health services so that it can reduce infant mortality related to asphyxia.